Furan diacid ester polymers, furan diacid ester polymer particles, and polymer articles

By controlling the characteristic index and average particle size, the general metal catalyst method is used to solve the problem of thermal cracking of polyfurandiformate in thermal processing, and polymer products with high processing thermal stability and economic benefits are achieved.

CN119505199APending Publication Date: 2025-02-25FAR EASTERN NEW CENTURY COPRRATION
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202410035465.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2023-08-22
Filing Date
2024-01-10
Publication Date
2025-02-25

AI Technical Summary

Technical Problem

Polyfurandiformate is prone to thermal cracking during thermal processing, resulting in ester bond fracture and affecting its performance. The existing methods use special aluminum catalysts, which are rigorous in operability and high cost.

Method used

By controlling the characteristic index and average particle size of the furanic acid ester polymer, condensation and polymerization reaction are carried out using a general metal catalyst to form furanic acid ester polymers and polymer particles with high processing thermal stability.

Benefits of technology

Thermal degradation phenomenon is reduced in thermal processing, the required performance of the polymer is maintained, the preparation cost is reduced, and the economic benefits of commercial mass production are improved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0004657540650000121
    Figure BDA0004657540650000121
  • Figure BDA0004657540650000122
    Figure BDA0004657540650000122
  • Figure BDA0004657540650000131
    Figure BDA0004657540650000131
Patent Text Reader

Abstract

The invention provides a furan diacid ester polymer, furan diacid ester polymer particles and a polymer product. The furan diacid ester polymer has a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value and the number average molecular weight of the furan diacid ester polymer) / (2 * 106)]. The furan diacid ester polymer has the advantage of processing thermal stability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to polyester, in particular to a furan diacid ester polymer, furan diacid ester polymer particles and polymer products. Background Art

[0002] Polyethylene terephthalate (PET) materials are widely used in daily necessities, such as PET bottles for carbonated beverages. However, due to the rise of environmental awareness in recent years, PET made from petrochemical raw materials has been widely replaced by bio-based polyester materials, such as polyethylene furanoate (PEF). However, since the structure of polyethylene furanoate is different from that of PET, the synthesis process, processing conditions and physical properties are also different. For example, in order to give polyester appropriate mechanical strength, a solid state polymerization process is used to increase the intrinsic viscosity and molecular weight of polyester. However, for PET, the solid state polymerization time only takes 3 to 5 hours, while for PET, the solid state polymerization time needs to be more than 20 hours.

[0003] In order to solve the problem of long solid-state polymerization time for polyethylene furandicarboxylate, U.S. Patent Publication No. 10590235 discloses a polyester, and the polyester is formed by a polymerization reaction of a reaction composition at 245°C to 270°C for 1.5 hours to 4 hours. The reaction composition comprises a furandicarboxylic acid component and ethylene glycol. The furandicarboxylic acid component comprises at least one of 2,5-furandicarboxylic acid and 2,5-furandicarboxylic acid dialkyl ester. The molar ratio of the furandicarboxylic acid component to the ethylene glycol is 1:1 to 1:4. The polyester has a number average molecular weight of 10,000 to 25,000, an acid value of 35 meq / kg to 70 meq / kg, a melting point of more than 215°C, and an intrinsic viscosity of 0.45 to 1.0 dL / g. The polyester can undergo solid-state polymerization and be converted into a high molecular weight polymer product in a short time.

[0004] U.S. Patent Publication No. 9890242 discloses a polyester, and the polyester is formed by a polymerization reaction of a reaction composition at 245°C to 270°C for 1.5 hours to 4 hours. The reaction composition comprises 2,5-furandicarboxylic acid and ethylene glycol, and the molar ratio of the 2,5-furandicarboxylic acid to the ethylene glycol is 1:1.01 to 1:1.15. The polyester has an acid value of 15 meq / kg to 122 meq / kg, an intrinsic viscosity of 0.45 to 1.0 dL / g, and a melting point of more than 215°C. The polyester can undergo solid-state polymerization and be converted into a high molecular weight polymer product in a short time.

[0005] U.S. Patent No. 11174344 discloses a poly(tetramethyl-2,5-furan dicarboxylate) polymer having a melting point of 168° C. to 175° C., a number average molecular weight of 40,000 or more, and an absorbance of 0.05 or more. The poly(tetramethyl-2,5-furan dicarboxylate) polymer can undergo solid state polymerization and be converted into a high molecular weight polymer product in a short time.

[0006] Although the polyesters of the patents can be rapidly converted into high molecular weight polymer products in solid state polymerization reactions, when the polyesters and polymer products of the patents are subjected to thermal processing, especially the melting process of the thermal processing, the polyesters and polymer products are still susceptible to ester bond breakage due to thermal cracking, thereby affecting the desired performance of the polyesters and polymer products. Therefore, the polyesters and polymer products have the problem of poor processing thermal stability.

[0007] In order to solve the above problems, Japanese Patent Publication No. 5928655 discloses a method for preparing polyfuran dicarboxylic acid ester, and in this method, a special aluminum catalyst is used in combination with a phosphorus stabilizer to obtain a polyfuran dicarboxylic acid ester with thermal stability. However, since the Japanese patent case uses a special aluminum catalyst, the reaction conditions for preparing the polyfuran dicarboxylic acid ester are relatively strict, resulting in severe limitations in operability. In addition, the high price of the aluminum catalyst causes the method to have a high process cost problem, and the aluminum catalyst is not easy to obtain, which is not conducive to commercial mass production needs.

[0008] In view of the above, for the industry in the field of polyester application, developing a polyester that can be prepared under common catalyst conditions and has thermal stability during thermal processing is an urgent problem to be solved. Summary of the invention

[0009] A first object of the present invention is to provide a furan diacid ester polymer.

[0010] The furan diacid ester polymer of the present invention has a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value of the furan diacid ester polymer and the number average molecular weight) / (2×10 6 )].

[0011] The furan diacid ester polymer of the present invention has an intrinsic viscosity variation value less than 0.85, and the intrinsic viscosity variation value is 0.245×[(X) -1.47 -(Y) -1.47], wherein X is the intrinsic viscosity of the furan diacid ester polymer, and Y is the intrinsic viscosity of the furan diacid ester polymer after being subjected to a condition, and the condition is to heat the furan diacid ester polymer so that the furan diacid ester polymer is in a molten state and keep the temperature constant in the molten state for 1 hour.

[0012] The furan diacid ester polymer of the present invention has an intrinsic viscosity variation value of 0.4 or more and less than 0.85.

[0013] The intrinsic viscosity of the furan diacid ester polymer of the present invention is greater than 0.55 dL / g.

[0014] The furan diacid ester polymer of the present invention is formed by reacting a reaction composition; the reaction composition includes a polycarboxyl component and a polyol component; the polycarboxyl component includes at least one first polycarboxyl material and the first polycarboxyl material is selected from a furan dicarboxylic acid material or a furan dicarboxylic acid diester material; the polyol component includes at least one C2 to C4 first polyol. Based on the total amount of the polyol component as 100 mol%, the total amount of the C2 to C4 first polyol is greater than 85 mol% and less than 100 mol%. Based on the total amount of the polycarboxyl component as 100 mol%, the total amount of the first polycarboxyl material is greater than 80 mol% and less than 100 mol%.

[0015] A second object of the present invention is to provide furan diacid ester polymer particles.

[0016] The furan diacid ester polymer particles of the present invention have a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value and the number average molecular weight of the furan diacid ester polymer particles) / (2×10 6 )], and the furan diacid ester polymer particles have an average particle size greater than 1.5 mm.

[0017] The furan diacid ester polymer particles of the present invention have an average particle size of greater than 1.5 mm and less than 6 mm.

[0018] The furan diacid ester polymer particles of the present invention have an average particle size of 1.8 mm to 6 mm.

[0019] The furan diacid ester polymer particles of the present invention have an intrinsic viscosity variation value of less than 0.85, and the intrinsic viscosity variation value is 0.245×[(X) -1.47 -(Y) -1.47 ], wherein X is the intrinsic viscosity of the furan diacid ester polymer particles, and Y is the intrinsic viscosity of the furan diacid ester polymer particles after being subjected to a condition, and the condition is to heat the furan diacid ester polymer particles so that the furan diacid ester polymer particles are in a molten state and keep the temperature constant in the molten state for 1 hour.

[0020] The furan diacid ester polymer particles of the present invention have an intrinsic viscosity variation value of 0.4 or more and less than 0.85.

[0021] The intrinsic viscosity of the furan diacid ester polymer particles of the present invention is greater than 0.55 dL / g.

[0022] The furan diacid ester polymer particles of the present invention are formed by reacting a reaction composition; the reaction composition includes a polycarboxyl component and a polyol component; the polycarboxyl component includes at least one first polycarboxyl material and the first polycarboxyl material is selected from furan dicarboxylic acid material or furan dicarboxylic acid diester material; the polyol component includes at least one C2 to C4 first polyol. Based on the total amount of the polyol component as 100 mol%, the total amount of the C2 to C4 first polyol is greater than 85 mol% and less than 100 mol%. Based on the total amount of the polycarboxyl component as 100 mol%, the total amount of the first polycarboxyl material is greater than 80 mol% and less than 100 mol%.

[0023] A third object of the present invention is to provide a polymer article.

[0024] The polymer article of the present invention comprises the furan diacid ester polymer described above.

[0025] The beneficial effect of the present invention is that, through the regulation of characteristic indexes, the furan diacid ester polymer of the present invention is not prone to ester bond rupture caused by thermal degradation during thermal processing, so that the desired performance of the furan diacid ester polymer can be maintained, and therefore, the furan diacid ester polymer has the advantage of processing thermal stability, thereby meeting the economic benefits of commercial mass production. In addition, through the regulation of characteristic indexes and average particle size, the furan diacid ester polymer particles of the present invention are less prone to ester bond rupture caused by thermal degradation during thermal processing, just like the furan diacid ester polymer. DETAILED DESCRIPTION

[0026] The present invention will be described in detail below.

[0027] <Furan diacid ester polymer>

[0028] The furan diacid ester polymer of the present invention comprises at least one of a furan diacid ester polyester and a solid polyester formed by solid-state polymerization of the furan diacid ester polyester. The furan diacid ester polyester is formed by condensation and polymerization of a reaction composition, and the reaction composition includes a polycarboxyl (-COO-) component and a polyol component.

[0029] In some embodiments of the present invention, the molar ratio of the polycarboxyl component to the polyol component is in a range of 1:1.1 to 1:3.0.

[0030] In some embodiments of the present invention, the polycarboxyl component includes at least one first polycarboxyl material, and the first polycarboxyl material is selected from furan dicarboxylic acid material or furan dicarboxylic acid diester material. The furan dicarboxylic acid material is, for example, but not limited to, 2,5-furan dicarboxylic acid or 2,4-furan dicarboxylic acid. The furan dicarboxylic acid diester material is, for example, but not limited to, 2,5-furan dicarboxylic acid dimethyl ester or 2,4-furan dicarboxylic acid dimethyl ester. In some embodiments of the present invention, the total amount of the polycarboxyl component is 100 mol%, and the total amount of the first polycarboxyl material is 80 mol% or more and less than 100 mol%. In some embodiments of the present invention, the polycarboxyl component also includes a second polycarboxyl material different from the first polycarboxyl material, and the second polycarboxyl material is, for example, but not limited to, terephthalic acid, isophthalic acid or sodium 5-sulfonate of isophthalic acid.

[0031] The polyol component includes at least one first polyol of C2 to C4. The first polyol of C2 to C4 is, for example, but not limited to, ethylene glycol. In some embodiments of the present invention, the total amount of the first polyol of C2 to C4 is 85 mol% or more and less than 100 mol%, based on the total amount of the polyol component as 100 mol%. In some embodiments of the present invention, the polyol component also includes a second polyol different from the first polyol of C2 to C4, and the second polyol is, for example, but not limited to, a polyol of C5 to C14.

[0032] In some embodiments of the present invention, the condensation and polymerization reactions are carried out in the presence of a metal catalyst. The metal catalyst is not particularly limited, and an existing catalyst for preparing polyester can be used. The metal catalyst can be used alone or in combination, and the metal catalyst is, for example, but not limited to, a manganese catalyst, a titanium catalyst, a germanium catalyst, an antimony catalyst or a zinc catalyst. The manganese catalyst is, for example, manganese acetate. The titanium catalyst is, for example, titanium citrate. The germanium catalyst is, for example, germanium dioxide. The antimony catalyst is, for example, antimony trioxide. The zinc catalyst is, for example, zinc acetate, etc. In some embodiments of the present invention, the amount of metal in the metal catalyst is greater than 200 mg, based on the total amount of the furan diacid polyester being 1 kg. In some embodiments of the present invention, the amount of metal in the metal catalyst is greater than 200 mg and less than 600 mg, based on the total amount of the furan diacid polyester being 1 kg.

[0033] The condensation and polymerization reaction includes a condensation reaction and a polymerization reaction. The condensation reaction is, for example, an esterification reaction or a transesterification reaction. In some embodiments of the present invention, the temperature of the condensation reaction is 200° C. to 250° C., and the time is 240 minutes to 360 minutes. In some embodiments of the present invention, the temperature of the polymerization reaction is 250° C. to 300° C., and the time is 130 minutes to 450 minutes.

[0034] In some embodiments of the present invention, the solid state polymerization reaction is carried out at a temperature of 130° C. to 220° C. and for a time of 48 to 120 hours. In some embodiments of the present invention, the solid state polymerization reaction is carried out for a time of 48 to 100 hours. In some embodiments of the present invention, the solid state polymerization reaction is carried out for a time of 60 to 100 hours.

[0035] In the present invention, the furan diacid ester polymer has a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value and the number average molecular weight of the furan diacid ester polymer) / (2×10 6 )]. In detail, in the present invention, the acid value and the number average molecular weight of the furan diacid ester polymer are taken into consideration at the same time, and the product of the two is controlled to achieve a balance between the acid value and the number average molecular weight, thereby obtaining the furan diacid ester polymer with processing thermal stability, and such consideration and design are unprecedented in the past.

[0036] In some embodiments of the present invention, the furan diacid ester polymer of the present invention has an intrinsic viscosity variation value less than 0.85, and the intrinsic viscosity variation value is 0.245×[(X) -1.47 -(Y) -1.47 ], wherein X is the intrinsic viscosity of the furan diacid ester polymer, and Y is the intrinsic viscosity of the furan diacid ester polymer after a condition, and the condition is heating the furan diacid ester polymer to make the furan diacid ester polymer in a molten state and keeping the temperature constant in the molten state for 1 hour. Specifically, the heating temperature to achieve the molten state is the melting point (Tm) of the furan diacid ester polymer + 20°C to the melting point of the furan diacid ester polymer + 60°C. In some embodiments of the present invention, the furan diacid ester polymer has an intrinsic viscosity variation value of greater than 0.4 and less than 0.85.

[0037] In some embodiments of the present invention, the intrinsic viscosity of the furan diacid ester polymer is greater than 0.55 dL / g. In some embodiments of the present invention, the intrinsic viscosity of the furan diacid ester polymer is greater than 0.55 dL / g and less than 1.3 dL / g.

[0038] <Furan diacid ester polymer particles>

[0039] The furan diacid ester polymer particles of the present invention have a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value and the number average molecular weight of the furan diacid ester polymer particles) / (2×10 6 )], and the furan diacid ester polymer particles have an average particle size greater than 1.5 mm.

[0040] Specifically, in the present invention, the acid value and the number average molecular weight of the furan diacid ester polymer particles are taken into consideration at the same time, and the product of the two is controlled to achieve a balance between the acid value and the number average molecular weight, and to match a suitable particle size, thereby obtaining the furan diacid ester polymer particles with better processing thermal stability. Such considerations and designs are unprecedented.

[0041] In some embodiments of the present invention, the furan diacid ester polymer particles of the present invention have an average particle size greater than 1.5 mm and less than 6 mm. In some embodiments of the present invention, the furan diacid ester polymer particles of the present invention have an average particle size of 1.8 mm to 6 mm. In detail, the average particle size of the furan diacid ester polymer particles is greater than 1.5 mm, so that compared with the average particle size of less than 1.5 mm, the furan diacid ester polymer particles have a smaller specific surface area, which can avoid the ester group of the furan diacid ester polymer particles from being exposed, thereby reducing the ester group from being directly heated, resulting in the phenomenon of thermal degradation of the furan diacid ester polymer particles, and the characteristic index of the furan diacid ester polymer particles is controlled at 0.27 to 0.55, which can further improve the processing thermal stability of the furan diacid ester polymer particles.

[0042] In some embodiments of the present invention, the furan diacid ester polymer particles of the present invention have an intrinsic viscosity variation value less than 0.85, and the intrinsic viscosity variation value is 0.245×[(X) -1.47 -(Y) -1.47 ], wherein X is the intrinsic viscosity of the furan diacid ester polymer particles, and Y is the intrinsic viscosity of the furan diacid ester polymer particles after a condition, and the condition is heating the furan diacid ester polymer particles to make the furan diacid ester polymer particles in a molten state and keeping the temperature constant in the molten state for 1 hour. Specifically, the heating temperature to achieve the molten state is the melting point (Tm) of the furan diacid ester polymer particles + 20°C to the melting point of the furan diacid ester polymer particles + 60°C. In some embodiments of the present invention, the furan diacid ester polymer particles have an intrinsic viscosity variation value of 0.4 or more and less than 0.85.

[0043] In some embodiments of the present invention, the intrinsic viscosity of the furan diacid ester polymer particles is greater than 0.55 dL / g. In some embodiments of the present invention, the intrinsic viscosity of the furan diacid ester polymer particles is greater than 0.55 dL / g and less than 1.3 dL / g.

[0044] The furan diacid ester polymer particles of the present invention may be formed from the components comprising the above-mentioned furan diacid ester polymer. In some embodiments of the present invention, the furan diacid ester polymer particles of the present invention comprise at least one of ester particles formed from the above-mentioned furan diacid ester polyester and solid polyester particles formed from the ester particles by solid state polymerization.

[0045] The component further comprises an additive. The additive may be a stabilizer, an antioxidant or a nucleating agent. The stabilizer may be a phosphite compound or a phosphate compound. The antioxidant may be a trialkyl phosphite, a mixture of an alkyl phosphite and an aromatic phosphite, an alkylated aromatic phosphite, a sterically hindered aromatic phosphite, an aliphatic spirocyclic phosphite, a sterically hindered phenyl spirocyclic phosphite, a sterically hindered bisphosphonites, an alkyl phosphate, an aromatic phosphate, a mixture of an alkyl phosphate and an aromatic phosphate, an alkyl phosphoacetate, a phenyl propionate, a hydroxyl benzyl, an alkylphenol, an aromatic amine, a hindered amine or hydroquinone.

[0046] The nucleating agent may be an inorganic mineral, an organic salt, a high melting point wax, or a polymer. The inorganic mineral may be talc, titanium dioxide, fused silica, boron nitride, mica, or calcium carbonate. The organic salt may be a fatty acid salt or an aromatic acid salt. The fatty acid salt may be a stearate. The stearate may be sodium stearate or zinc stearate. The aromatic acid salt may be benzoate, aromatic phosphate, isophthalic acid sulfonate, saccharin sodium salt, furandicarboxylic acid disodium salt, commercially available Phosphate salt of 3988, commercially available The phosphate ester salt of NX88, the phosphate ester salt of the commercial product NA-11 or the phosphate ester salt of the commercial product NA-21, etc. The high melting point wax is for example stearamide wax, erucamide wax or bisamide wax, etc. The polymer is for example ionomer, polyethylene glycol, polyethylene terephthalate or polybutylene terephthalate, etc. The ionomer is for example the ionomer of the Surlyn series of DuPont or the ionomer of the Aculyn series of Rohm and Haas, etc.

[0047] The furan diacid ester polymer particles and furan diacid ester polymer of the present invention can be used to form polymer products such as packaging containers or packaging films.

[0048] <Polymer products>

[0049] The polymer article of the present invention comprises a furan diacid ester polymer, and the polymer article is formed into, for example, fibers, packaging containers, packaging films, or oriented tapes for bundling, and the packaging containers are, for example, bottles.

[0050] The present invention will be further described with reference to the following examples, but it should be understood that the examples are only for illustration and should not be construed as limitations on the implementation of the present invention.

[0051] Example 1

[0052] 465 grams of dimethyl 2,5-furandicarboxylate, 376 grams of ethylene glycol, 0.023 grams of phosphoric acid, 0.138 grams of antimony trioxide and 0.129 grams of zinc acetate were mixed to form a mixture. The mixture was heated to 235°C and an esterification reaction was carried out for 4 hours under a nitrogen environment, and methanol was distilled off at the same time. Then, a polymerization reaction was carried out for 227 minutes under the conditions of a temperature of 250°C and a pressure of 0.8 torr to obtain furan diacid polyester. The furan diacid polyester was subjected to strip drawing and cutting to obtain furan diacid polyester particles with an intrinsic viscosity (IV) of 0.566 dL / g and an average particle size of 3.7 mm. Among them, based on the total amount of the furan diacid polyester being 1 kg, the amount of phosphoric acid was 50 mg, the amount of antimony trioxide was 300 mg and the amount of zinc acetate was 280 mg.

[0053] Examples 2 to 9 and Comparative Examples 1 to 6

[0054] The preparation methods of furan diacid polyester particles of Examples 2 to 9 and Comparative Examples 1 to 6 are substantially the same as those of Example 1, with the main differences being that in Example 8 and Comparative Example 5, the zinc acetate of Example 1 is replaced by 0.006912 g of a titanium catalyst (brand: Borica; model: AQ5000), and the amount of the titanium catalyst is 15 mg based on the total amount of the furan diacid polyester being 1 kg. In Example 9 and Comparative Example 6, the 2,5-furan dicarboxylic acid dimethyl ester of Example 1 is replaced by 394 g of 2,5-furan dicarboxylic acid and the amount of ethylene glycol is replaced from 376 g to 188 g, and zinc acetate is not contained. The polymerization reaction temperature of Examples 2 to 9 and Comparative Examples 1 to 6 is all 250° C., and the reaction time is 193 minutes, 191 minutes, 173 minutes, 390 minutes, 356 minutes, 430 minutes, 203 minutes, 135 minutes, 230 minutes, 200 minutes, 415 minutes, 172 minutes, 233 minutes and 155 minutes, respectively, and the pressure is 0.78 torr, 0.75 torr, 0.8 torr, 0.81 torr, 0.72 torr, 0.85 torr, 0.81 torr, 0.78 torr, 0.82 torr, 0.85 torr, 0.73 torr, 0.72 torr, 0.85 torr and 0.82 torr, respectively.

[0055] Example 10

[0056] The furan diacid polyester pellets of Example 1 were subjected to a solid state polymerization reaction at 195° C., normal pressure and nitrogen environment for 96 hours to obtain solid polyester pellets having an intrinsic viscosity of 1.03 dL / g and an average particle size of 3.7 mm.

[0057] Examples 11 to 18 and Comparative Examples 7 to 11

[0058] The preparation methods of the solid-state polymerization polyester particles of Examples 11 to 18 and Comparative Examples 7 to 11 are substantially the same as that of Example 10, with the main difference being that the type of furan diacid polyester particles and the solid-state polymerization reaction time are changed.

[0059] Evaluation Project

[0060] The furan diacid polyester pellets of Examples 1 to 9 and Comparative Examples 1 to 6 and the solid polyester pellets of Examples 10 to 18 and Comparative Examples 7 to 11 were subjected to the following tests. For the sake of clarity, the test procedures of the following test items are described using the furan diacid polyester pellets of Example 1 as a representative.

[0061] Intrinsic viscosity (unit: dL / g) measurement: Measured according to ASTM D4603 (2018 edition) Standard Test Method for Determining Intrinsic Viscosity of Polyethylene Terephthalate Using Glass Capillary Viscometer. The furan diacid polyester pellets of Example 1 were added to a solvent component containing 60 wt% of phenol and 40 wt% of 1,1,2,2-tetrachloroethane to form a mixed solution, wherein the concentration of the furan diacid polyester pellets in the mixed solution was 3.25 g / L. Then, the mixed solution was heated at 110±10°C for 20 minutes, and then cooled to form a sample to be tested. The sample to be tested was measured at 30° C. using a viscometer (brand: CANNON; model: MiniPV-HX) to obtain relative viscosity, and then the relative viscosity was substituted into the Billmyer equation to calculate the intrinsic viscosity, and the Billmyer equation is {relative viscosity-1+3×ln(relative viscosity)} / (4×the concentration of the furan diacid polyester particles in the mixed solution).

[0062] Measurement of average particle size (unit: mm): 300 g of the furan diacid ester polyester particles of Example 1 were screened using KUANG YANG stainless steel standard analysis sieves of different mesh sizes, and the weight of the furan diacid ester polyester particles screened by the KUANG YANG stainless steel standard analysis sieves of each mesh size was recorded. Then, the average particle size of the furan diacid ester polyester particles was calculated based on the mesh size and weight.

[0063] Measurement of number average molecular weight: 0.04 g to 0.08 g of furan diacid polyester particles of Example 1 are dissolved in 0.5 mL of hexafluoroisopropanol at room temperature to obtain a first mixture. Chloroform and chlorophenol are mixed in a volume ratio of 1:1 to obtain 4.5 mL of a second mixture. The first mixture is mixed with the second mixture to obtain a test sample. The test sample is introduced into a gel permeation chromatograph (brand: waters; model: 2695) for detection. The column of the gel permeation chromatograph is Shodex K-803 or Shodex K-802, and the detection temperature is 40°C.

[0064] Acid value (unit: meq / kg) measurement: Measured according to the standard test method for the terminal carboxyl content of polyethylene terephthalate (PET) yarn of ASTM D7409 (2020 edition). Add 3 to 5 drops of bromophenol blue indicator to 25 mL of solvent component (including phenol and chloroform, and the weight content ratio of the phenol to the chloroform is 3:2), then add titrant [potassium hydroxide solution (including benzyl alcohol and potassium hydroxide with a concentration of 0.1N)] until the color completely changes to blue, which is the titration endpoint, and record the amount of potassium hydroxide added in the titrant at the titration endpoint (V0, mL). 2 to 4 grams of the furan diacid polyester particles of Example 1 are used as a test sample, and the test sample is dissolved in 25 mL of a solvent component (including phenol and chloroform, and the weight content ratio of the phenol to the chloroform is 3:2) to form a mixed solution, and then 3 to 5 drops of bromophenol blue indicator are added, followed by adding a titrant [potassium hydroxide solution (including benzyl alcohol and potassium hydroxide with a concentration of 0.1N)] until the color completely changes to blue, which is the titration end point, and the amount of potassium hydroxide added in the titrant at the titration end point is recorded (V1, mL). Then, the acid value is calculated using a formula, and the formula is [(V1-V0)×N×1000] / weight of the test sample (gram), where N is the equivalent concentration of potassium hydroxide.

[0065] Calculation of characteristic index: [(product of the acid value and number average molecular weight of the furan diacid polyester particles of Example 1) / (2×10 6 )].

[0066] Measurement of intrinsic viscosity variation: 1.0 g of the furan diacid polyester pellets of Example 1 were dried at 100°C for 10 minutes, then the temperature was raised in an air environment until the furan diacid polyester pellets were in a molten state, then the temperature was maintained at the molten state for 1 hour, then liquid nitrogen was used for instant cooling, and then the pellets were placed in an oven set at 50°C for drying to remove moisture and obtain a dried product. The dried product was subjected to the above-mentioned intrinsic viscosity measurement to obtain the intrinsic viscosity (Y, dL / g). The intrinsic viscosity (X, dL / g) of the furan diacid polyester pellets of Example 1 and the intrinsic viscosity of the dried product were substituted into 0.245×[(X) -1.47 -(Y) -1.47 ], the intrinsic viscosity variation value is obtained. Among them, the melting points of the furan diacid polyester pellets of Examples 1 to 9 and Comparative Examples 1 to 6 are 204°C, 198°C, 197°C, 195°C, 197°C, 201.5°C, 197°C, 199°C, 200°C, 205°C, 196°C, 197°C, 196°C, 196°C and 203°C, respectively, and the melting points of the solid polyester pellets of Examples 10 to 18 and Comparative Examples 7 to 11 are 215°C, 212°C, 210°C, 206°C, 205°C, 215°C, 210°C, 216°C, 215°C, 211°C, 208°C, 206°C, 208°C and 212°C, respectively. The heating temperature for achieving the molten state of Examples 1 to 18 and Comparative Examples 1 to 11 is 250°C.

[0067] The calculation of the intrinsic viscosity increase rate [unit: (ΔdL / g) / hr] is as follows: [intrinsic viscosity of the solid-polymerized polyester pellets of Example 10 (11, 12, 13, 14, 15, 16, 17, 18) - intrinsic viscosity of the furan diacid polyester pellets of Example 1 (2, 3, 4, 5, 6, 7, 8, 9)] / solid-state polymerization reaction time of Example 10 (11, 12, 13, 14, 15, 16, 17, 18). [intrinsic viscosity of the solid-polymerized polyester pellets of Comparative Example 7 (8, 9, 10, 11) - intrinsic viscosity of the furan diacid polyester pellets of Comparative Example 1 (2, 3, 5, 6)] / solid-state polymerization reaction time of Comparative Example 7 (8, 9, 10, 11).

[0068] Table 1

[0069]

[0070] Table 2

[0071]

[0072] From the data in Table 1 and Table 2, it can be seen that the characteristic indexes of the furan diacid ester polyester pellets of Examples 1 to 9 are 0.27 to 0.55, while the characteristic indexes of the furan diacid ester polyester pellets of Comparative Examples 1 to 3 and Comparative Examples 5 to 6 are less than 0.27 or greater than 0.55, resulting in the intrinsic viscosity variation values ​​of the furan diacid ester polyester pellets of Examples 1 to 9 being 0.445 to 0.846, while the intrinsic viscosity variation values ​​of the furan diacid ester polyester pellets of Comparative Examples 1 to 3 and Comparative Examples 5 to 6 being 0.988 to 1.231. It can be seen that the furan diacid ester polyester pellets of the present invention are not prone to the problem of molecular breakage caused by thermal degradation during thermal processing. In addition, the average particle size of the furan diacid polyester particles of Comparative Example 4 is less than 1.5 mm, resulting in a greater variation value of the intrinsic viscosity of the furan diacid polyester particles of Comparative Example 4 than that of the furan diacid polyester particles of Examples 1 to 9. It can be seen that, compared with Comparative Example 4, under the condition that the average particle size of the furan diacid polyester particles of the present invention is greater than 1.5 mm and the characteristic index is 0.27 to 0.55, the furan diacid polyester particles of the present invention do have good processing thermal stability.

[0073] Table 3

[0074]

[0075] Table 4

[0076]

[0077] It can be seen from the data in Tables 3 and 4 that the characteristic indexes of the solid polyurethane polyester pellets of Examples 10 to 18 are 0.27 to 0.55, while the characteristic indexes of the solid polyurethane polyester pellets of Comparative Examples 7 to 11 are less than 0.27 or greater than 0.55, resulting in the characteristic viscosity variation values ​​of the solid polyurethane polyester pellets of Examples 10 to 18 being 0.454 to 0.688, while the characteristic viscosity variation values ​​of the solid polyurethane polyester pellets of Comparative Examples 7 to 11 being 0.892 to 1.058. It can be seen that the solid polyurethane polyester pellets of the present invention are not prone to the problem of molecular breakage due to thermal degradation during thermal processing.

[0078] In summary, when the furan diacid ester polymer particles and furan diacid ester polymers having characteristic indexes of 0.27 to 0.55 of the present invention are subjected to heat processing, the problem of ester bond breakage due to thermal degradation is not likely to occur, so that the desired properties of the furan diacid ester polymer particles and furan diacid ester polymers can be maintained. Therefore, the furan diacid ester polymer particles and furan diacid ester polymers do have the advantage of processing thermal stability, thereby meeting the economic benefits of commercial mass production, and thus can indeed achieve the purpose of the present invention.

Claims

1. A furan diacid ester polymer, characterized in that: The furan diacid ester polymer has a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value of the furan diacid ester polymer and the number average molecular weight) / (2×10 6 )].

2. The furan diacid ester polymer according to claim 1, characterized in that: The furan diacid ester polymer has an intrinsic viscosity variation value less than 0.85, and the intrinsic viscosity variation value is 0.245×[(X) -1.47 -(Y) -1.47 ], wherein X is the intrinsic viscosity of the furan diacid ester polymer, and Y is the intrinsic viscosity of the furan diacid ester polymer after being subjected to a condition, and the condition is to heat the furan diacid ester polymer so that the furan diacid ester polymer is in a molten state and keep the temperature constant in the molten state for 1 hour.

3. The furan diacid ester polymer according to claim 2, characterized in that: The furan diacid ester polymer has an intrinsic viscosity variation value of 0.4 or more and less than 0.

85.

4. The furan diacid ester polymer according to claim 1, characterized in that: The furanoic acid ester polymer has an intrinsic viscosity greater than 0.55 dL / g.

5. The furan diacid ester polymer according to claim 1, characterized in that: The furan diacid ester polymer is formed by reacting a reaction composition; the reaction composition includes a polycarboxyl component and a polyol component; the polycarboxyl component includes at least one first polycarboxyl material and the first polycarboxyl material is selected from furan dicarboxylic acid material or furan dicarboxylic acid diester material; the polyol component includes at least one C2 to C4 first polyol, the total amount of the C2 to C4 first polyol is greater than 85 mol% and less than 100 mol%, and the total amount of the polycarboxyl component is greater than 100 mol%, and the total amount of the first polycarboxyl material is greater than 80 mol% and less than 100 mol%.

6. A furan diacid ester polymer particle, characterized in that: The furan diacid ester polymer particles have a characteristic index of 0.27 to 0.55, and the characteristic index is [(the product of the acid value of the furan diacid ester polymer particles and the number average molecular weight) / (2×10 6 )], and the furan diacid ester polymer particles have an average particle size greater than 1.5 mm.

7. The furan diacid ester polymer particles according to claim 6, characterized in that: The furandioic acid ester polymer particles have an average particle size of greater than 1.5 mm and less than 6 mm.

8. The furan diacid ester polymer particles according to claim 7, characterized in that: The furanoic acid ester polymer particles have an average particle size of 1.8 mm to 6 mm.

9. The furan diacid ester polymer particles according to claim 6, characterized in that: The furan diacid ester polymer particles have an intrinsic viscosity variation value less than 0.85, and the intrinsic viscosity variation value is 0.245×[(X) -1.47 -(Y) -1.47 ], wherein X is the intrinsic viscosity of the furan diacid ester polymer particles, and Y is the intrinsic viscosity of the furan diacid ester polymer particles after being subjected to a condition, and the condition is to heat the furan diacid ester polymer particles so that the furan diacid ester polymer particles are in a molten state and keep the temperature constant in the molten state for 1 hour.

10. The furan diacid ester polymer particles according to claim 9, characterized in that: The furan diacid ester polymer particles have an intrinsic viscosity variation value of 0.4 or more and less than 0.

85.

11. The furan diacid ester polymer particles according to claim 6, characterized in that: The furanoic acid ester polymer particles have an intrinsic viscosity greater than 0.55 dL / g.

12. The furan diacid ester polymer particles according to claim 6, characterized in that: The furan diacid ester polymer particles are formed by reacting a reaction composition; the reaction composition includes a polycarboxyl component and a polyol component; the polycarboxyl component includes at least one first polycarboxyl material and the first polycarboxyl material is selected from furan dicarboxylic acid material or furan dicarboxylic acid diester material; the polyol component includes at least one C2 to C4 first polyol, and based on the total amount of the polyol component as 100 mol%, the total amount of the C2 to C4 first polyol is greater than 85 mol% and less than 100 mol%, and based on the total amount of the polycarboxyl component as 100 mol%, the total amount of the first polycarboxyl material is greater than 80 mol% and less than 100 mol%.

13. A polymer product, characterized in that: The polymer article comprises: the furan diacid ester polymer according to any one of claims 1 to 5.

Citation Information

Patent Citations

  • Flaw detection method of metallic material

    JP1984028655A

  • Process for the preparation of a polyester

    US10590235B2

  • Process for the production of a solid-state polymerized poly (tetramethylene-2, 5-furan dicarboxylate) polymer and polymer thus produced

    US11174344B2

  • Polyester and method for preparing such a polyester

    US9890242B2